The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1371/journal.pone.0129466
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Expression of Prostaglandin E2 (PGE2) Synthesis and Degradation Enzymes during Differentiation of Immortalized Urothelial Cells from Patients with Interstitial Cystitis/Painful Bladder Syndrome

Abstract: PurposeThe differentiated superficial cells of the urothelium restrict urine flow into the bladder wall. We have demonstrated that urothelial cells isolated from bladders of patients with interstitial cystitis/painful bladder syndrome (IC/PBS) fail to release PGE2 in response to tryptase. This study examines the expression of PGE2 synthesis and degradation enzymes in urothelial cells during differentiation.Materials and MethodsWe measured immunoprotein expression of cyclooxygenase-2 (COX-2), prostaglandin E2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
1
0
2
Order By: Relevance
“…have shown that the expression levels of PGE2 and EP1/2 mRNA are significantly higher in BPS/IC patients4. Several studies have also suggested that the PGE2/EP1/EP2 pathway is involved in the development of BPS/IC416. Importantly, the results of Takahashi’s study showed that PGE2 can regulate the expression of ICAM-1 via the EP2 receptor17.…”
Section: Discussionmentioning
confidence: 99%
“…have shown that the expression levels of PGE2 and EP1/2 mRNA are significantly higher in BPS/IC patients4. Several studies have also suggested that the PGE2/EP1/EP2 pathway is involved in the development of BPS/IC416. Importantly, the results of Takahashi’s study showed that PGE2 can regulate the expression of ICAM-1 via the EP2 receptor17.…”
Section: Discussionmentioning
confidence: 99%
“…В клетках толстого восходящего отдела петли Генле они снижают реабсорбцию ионов натрия, хлора [36] и ионов магния [37]. кроме того, у пациенток с недержанием мочи выявлена повышенная экскреция простаглан-дина е 2 с мочой [38][39][40].…”
Section: обсуждение результатовunclassified
“…В клет-ках толстого восходящего отдела петли Генле они снижают реабсорбцию ионов Na, Cl [36] и ионов магния [37]. Кроме того, у пациенток с недержанием мочи выявлена повышенная экскреция простагландина Е 2 с мочой [38][39][40]. В группе пациенток с недержанием мочи, по-лиурией или никтурией и отсутствием эффек-та от применения десмопрессина был исполь-зован блокатор синтеза простагландинов -диклофенак натрия, что позволило добиться положительного эффекта и нормализовать ритм мочеобразования у 75,0 ± 6,5 % пациен-ток [13].…”
Section: обсуждение результатовunclassified